Conjugated Block Copolymers: Formation of Hierarchical Architectures with Dimensional and Morphological Control in the Self‐Assembly of Conjugated Block Copolymers (Small Methods 2/2020). Issue 2 (12th February 2020) - Wang, Meijing; Han, Liang; Zhu, Yulin; Qi, Rui; Tian, Leilei; He, Feng
Abstract : In article number 1900470 by Leilei Tian, Feng He, and co‐workers, conjugated block copolymers (PPV7 ‐ b ‐P2 VP n ) are utilized as building blocks for self‐assembly and the hierarchical scarf‐like architectures are realized through a facile solution‐processed approach. By adjusting the block ratio of BCPs and solvent polarity, the dimensinality and morphology of micelles are controlled. The formation of these micelles is mainly driven by intermolecular π–π interactions between PPV blocks.